ISOLASI DAN UJI AKTIVITAS ANTIOKSIDAN SENYAWA FLAVONOID DARI EKSTRAK DAUN JAMBU BIJI PUTIH (Psidium guajava Linn) - Egi Azikin Maulana; I. A. R. Astiti Asih; Made Arsa (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2016)
Antioxidant is molecules that can inhibit the activity of free radical. White guava (Psidium guajava Linn) is one of many plants that have potential as antioxidant. This research was aimed to identify the flavonoid compounds and to determine IC50 values in the white guava leaf extract. Extraction was done by maceration method. The separation and purification was done by TLC and coloumn chromatography method. Flavonoid compound was identified using FTIR and UV-Vis spectrofotometry and antioxidant activity was tested with DPPH method. A 1000 grams of white guava leaf powder was extracted by n-hexane produced 103,40 grams of concentrated n-hexane extract and extraction procces by ethanol 70 % produced 128,49 grams of concetrated etanol extract. Eighty grams of ethanol extract partition produced 1.01 grams of n-hexane extract, 1.95 grams of chloroform extract, and 3.77 grams of n-butanol extract. The results of phytochemical test indicated that n-butanol extract positively contained flavonoids. The results of antioxidant activity towards DPPH from n-butanol extract showed IC50 of 37,14 ppm. The separation and purification n-butanol extract with n-hexane : ethyl acetate : n-butanol (8:2:1) as the eluent resulted 5 fractions (A, B, C, D, E), with C fraction positively contained flavonoids. FTIR analysis showed C isolates contained functional groups of CH aliphatic, CH aromatic, C = C aromatic, C = O, OH, and C - O. C fraction was analyzed with UV-Vis showing 2 peaks at ? 347.30 nm (band I) and ? 278.50 nm (band II) suggesting the presence of flavones group with possibility of OH groups attached to C-3, C-2’ atoms, ortho-dihydroxy groups attached to C-5', C- 6; C-4', C-5', and O-glycoside group at C-7 atom.